Trans-esophageal endobronchial ultrasound-guided needle aspiration (EUS-B-NA): a road map for the chest physician - Bugalho, António; Eberhardt, Ralf (Revista portuguesa de pneumologia. English Edition, 2018)
The endobronchial ultrasound (EBUS) scope has been increasingly used in the gastrointestinal tract (EUS-B). Scientific data proves its efficacy and safety to provide a complete lung cancer staging, when combined with EBUS-TBNA, and in the diagnosis of para-esophageal lesions. There are multiple barriers to start performing EUS-B but probably the most important ones are related to knowledge and training, so new operators should follow a structured training curriculum. This review aims to reflect the best current knowledge regarding EUS-B and provide a road map to assist those who are incorporating the technique into their clinical practice.